Influence of Promotions on Sales at The Erafone Store Sumedang - Firmansyah, Gugum Aji; Kurniasih, Nining; Damayanti, Wulan Ariani; Kurniawan, Robi; Supranata, Yogi; Crisca, Rini (Journal of Bussines Management Basic, 2024)
This study aims to determine the extent of the influence of promotions on sales at Erafone Store Sumedang. The research uses a descriptive method with a sample size of 97 respondents. The data source used is secondary data in the form of sales reports from the last three years, 2020-2023. The results of the study show that the implementation of promotions carried out by Erafone is very good, falling into the "strongly agree" category with a score of 6.348, and the implementation of sales carried out by Erafone is also very good, falling into the "strongly agree" category with a score of 6.452. The data analysis techniques used include simple linear regression analysis, correlation analysis, and determination analysis. The results of this study indicate that promotions have a positive and significant effect on sales at Erafone Store Sumedang, with a correlation coefficient of 0.575 or 57.5%. The result of the determination coefficient is 0.331 or 33.1%. The results of the t-test show that t calculated 6.850 > t_table 1.98525, indicating that promotions have a positive effect on sales.